The Chronology of Early Human Settlement in Three Gorges Region, China—Contribution of Coupled Electron Spin Resonance and Uranium-Series Dating Method - Han, Fei; Bahain, Jean-Jacques; Shao, Qingfeng; Sun, Xuefeng; Voinchet, Pierre; Xiao, Ping; Huang, Manchen; Li, Mengqi; Yin, Gongming (Frontiers in Earth Science, 2022)
The Three Gorges region (TGR) located in the geographic center of China, is a transition zone between mountain and plain areas, and a probable migration corridor for hominins and other mammals between South and North China. Detailed chronological information of paleoanthropological evidence in this area could help us better understand the human evolution in East Asia. The OSL and U-series dating methods are two conventional dating methods generally adopted to date such sites; however, their applications were limited by the dating range—restricted to several hundred of millennia and ambiguous stratigraphic relationship between the archaeological remains and the dating target materials. Cosmogenic nuclide burial dating of quartzite stone artifacts and coupled electron spin resonance and uranium series dating (ESR/U-series) of fossil teeth have the potential to date Early–Middle Pleistocene hominin sites in Asia and were applied increasingly in China in recent years. However, the application of cosmogenic 26Al/10Be burial dating is limited in TGR because most sites are dominated by limestone, leading to the scarcity of the quartz component. In this case, the coupled ESR/U-series method plays a more important role in the establishment of the chronology of human settlement. In TGR, by using the coupled ESR/U-series method, we have dated seven important Early and Middle Pleistocene hominin settlement sites, including Longgupo, Jianshi, Yunxian, Meipu, Bailongdong, Changyang, and Yumidong sites. Based on our dating results, we propose that hominins were settled in TGR probably from the early stage of Early Pleistocene (∼2.5−2.2 Ma) at the Longgupo site to the late Middle Pleistocene to Late Pleistocene of the Yumidong site (∼274−14 ka) and very likely to spread to other parts of East Asia during this time period. In view of the potential of coupled ESR/U-series dating on fossil teeth from the hominin sites in the TGR, future work may consider the micro damage or non-destructive analysis of enamel fragment with the ESR method and laser ablation ICP-MS techniques that will make possible the direct dating of precious human fossils in China.